Relationships between Budgetary Participation and Organizational Commitment: Mediated by Reinforcement Contingency Evidence from the Service Sector Industries - Selvina, Mia; Yuliansyah, Yuliansyah (Universitas Prasetiya Mulya, 2015)
The purpose of this study is to examine the relationship, mediated through reinforcement contingency, between (a) participation in budgeting, and (b) organizational commitment, of those organizations in the service industry, listed in the Indonesian Stock Exchange and also having their branch offices in Bandar Lampung. We develop a new construct of reinforcement contingency, through focus group discussion and several pilot studies, and use it in the main survey. We analyse data from 42 respondents, using SmartPLS. We find that reinforcement contingency as the mediation variable affects the relation between participation in budgeting and organizational commitment. This study suggests the “no reward and no punishment” system as the appropriate reinforcement contingency for employees, in order to enhance their commitment to their organization.